2007
DOI: 10.1007/s10804-007-9032-5
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents in Transition to Adulthood: Parental Support, Relationship Satisfaction, and Post-transition Adjustment

Abstract: The transition from high school is a pivotal period for intergenerational relations, as the asymmetry characterizing pre-transition relations with parents is reconfigured. Changes in adolescent-parent relations across this transition have potentially important implications for post-transition adjustment. A prospective study was conducted with an ethnically diverse sample that included adolescents who were not college-bound. Maternal, but not paternal, relations improved across the transition from high school t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 27 publications
5
57
0
Order By: Relevance
“…This was particularly so early on in the transition process (Jones et al 2006). Levitt, Silver and Santos (2007) also found parents to play an important role in successful transitions whereby having a satisfactory relationship with one's parents was found to be predictive of psychological adjustment. Likewise, Knoester's (2003) structural equation modelling study of a representative sample of youth and their parents from the United States also revealed that the quality of the parent-child relationship and the parents' own sense of well-being were both predictive of children's well-being during young adulthood.…”
Section: Role Of Parents In the Transition Processmentioning
confidence: 93%
“…This was particularly so early on in the transition process (Jones et al 2006). Levitt, Silver and Santos (2007) also found parents to play an important role in successful transitions whereby having a satisfactory relationship with one's parents was found to be predictive of psychological adjustment. Likewise, Knoester's (2003) structural equation modelling study of a representative sample of youth and their parents from the United States also revealed that the quality of the parent-child relationship and the parents' own sense of well-being were both predictive of children's well-being during young adulthood.…”
Section: Role Of Parents In the Transition Processmentioning
confidence: 93%
“…Higher levels of maternal closeness increased the odds of providing economic and housing support at age 24, leading the researchers to conclude that "those who were closer to their mothers also received other types of parental aid… that could have contributed to their ability to become selfsufficient" (p. 426). A prospective longitudinal study by Levitt, Silver, and Santos (2007) found that changes in support post-high school to college transition positively predicted and accounted for the most variance in posttransition relationship satisfaction with parents. Because post-and not pre-transition support was related to relationship satisfaction, the authors concluded that the college transition provided impetus for changes in family relationships.…”
Section: Developmental Psychology Literature Characterizing Parental mentioning
confidence: 99%
“…Beginning in early adolescence and enduring until young adulthood, adolescents have self-reported closer, more satisfied relationships with mothers compared to fathers (Levitt et al, 2007; Thornton et al, 1995), marked by equal responsibility and friendliness in comparison to father-adolescent relationships (Pipp et al, 1985). When parent-adolescent relationships are viewed during the transition from adolescence into young adulthood after high school, similar trends in relationship quality can be seen.…”
Section: Family Relationship Change Over Timementioning
confidence: 99%